Thermal pretreatment of poplar sawdust at 100 °C in water or with microwave heating impacts the pyrolysis behaviors - Li, Chao; Li, Baihong; Gao, Guoming; Zhang, Lijun; Zhang, Shu; Zhang, Lei; Xiang, Jun; Hu, Song; Wang, Yi; Hu, Xun (Journal of industrial and engineering chemistry (Seoul, Korea), 2023)
[Display omitted] •Cooking/microwave heating at 100 °C enhances carbon content of poplar sawdust.•Pretreatments promote carbonization in pyrolysis, forming more biochar/bio-oil.•Pretreatment enhances C content of biochar via accelerated deoxygenation.•Pretreatments renders biochar of higher thermal stability, crystallinity and aromatic degree.•Pretreatments affect evolution of O-containing intermediates and facilitate aromatization. Drying at 100 °C is a common practice for processing many biomasses for their further thermochemical conversion via the routes such as pyrolysis. The drying temperature of 100 °C is low, but might not be too low to cause any impact on pyrolytic behaviors of a biomass feedstock. In this study, varied scenarios of thermal pretreatment of poplar sawdust (oven-drying, boiling in water and microwave heating) at 100 °C were screened for probing their potential influence on the pyrolytic behaviors at 500 and 750 °C. Comparing with oven-drying, boiling in water (cooking) and microwave heating at 100 °C could remove some oxygen-containing species, increasing carbon content of the pretreated sawdust and promoting carbonization in pyrolysis. This enhanced formation of biochar, heavy π-conjugated organics in bio-oil, but suppressed generation of gas. The cooking or microwave heating pretreatment also promoted aromatization to form the biochar of higher thermal stability, higher crystallinity, and higher aromatic degree, due to the enhanced deoxygenation reactions in the pyrolysis. The in-situ IR characterization suggested that microwave pretreatment promoted generation of unsaturated ketones and also the species with olefinic C = C, favoring their further aromatization. The cooking pretreatment impacted transformation routes of the oxygen-containing organics, thus modifying pyrolysis behaviors of the pretreated sawdust.